NANOTECHNOLOGY IN PAEDIATRIC DRUG DELIVERY: ADVANCES, CHALLENGES, AND REGULATORY CONSIDERATIONS-A REVIEW - ANGAMUTHU, GOWTHAM; MAHADEVSAMY, GIRIDHARA; SIVANATHAN, GURUBARAN; RAJAGOPAL, SANJAI; DHANDAPANI, NAGASAMY VENKATESH (International Journal of Applied Pharmaceutics, 2025)
Children's growth and physiology are basically different from that of adults, so paediatric pharmacotherapy is dissimilar in challenge. The traditional formulations of medicines are not suitable for children, as they face issues of poor taste, insusceptibility of dosage flexibility, and potential miscalculation of dosage. Nanotechnology of nanoscale dimensions holds great promise in solving paediatric drug delivery issues. In this article, the prospect of nanocarriers, such as liposomes, polymeric nanoparticles, and solid lipid nanoparticles, is discussed in paediatric medicine. Nanoformulations have been found to increase oral bioavailability by 60% and decrease dosing frequency by 50%, with improved therapeutic response in paediatric patients. Today, at least four FDA-approved nanoformulations are on the market for paediatric applications, such as liposomal amphotericin B for fungal infections and pegylated liposomal doxorubicin for paediatric oncology, showing the increasing clinical use of nanotechnology in paediatric medicine. However, there are huge challenges remaining: long-term safety of nanomaterials in developing organisms, scalable manufacturing, regulatory hurdles, and ethical considerations for paediatric clinical trials. The review will highlight the continued need for interdisciplinarity to overcome the challenges and reach the potential of nanotechnology for enhancing paediatric health outcomes. Future directions include stimuli-responsive and personalized nanocarriers, combination therapy, and theranostic nanoparticles. With further research and development, nanotechnology can potentially revolutionize paediatric pharmacotherapy with more effective, safer, and patient-compliant drug delivery.